Antiproliferative effect of Solanum nigrum L. water extract on breast can-cer cells: potential roles of apoptosis and oxidative stress: Antiproliferative effect of Solanum nigrum on breast cancer cells - Khan, Haseeb A.; Prasad, N. Rajendra; Alrokayan, Salman H.; Alghamdi, Amani A. (Cellular and Molecular Biology, 2023)
Breast cancer is the most progressive cancer among women worldwide. The currently available chemotherapeutic agents induce severe unacceptable adverse effects in breast cancer patients. In this context, natural medicinal herbs are gaining importance to find non-toxic effective anticancer drugs. Solanum nigrum is one of the major traditional medicinal plants widely used in Ayurveda for the treatment of various diseases. This study investigated the anticancer effect of Solanum nigrum water extract (SNWE) against MCF-7 and triple-negative MDA-MB-231 breast cancer cell lines. SNWE significantly induced oxidative stress-mediated apoptotic cell death in a concentration-dependent manner. Real-time PCR results illustrated the upregulation of proapoptotic genes and downregulation of antiapoptotic genes after SNWE treatment in MCF-7 and MDA-MB-231 cell lines. Immunofluorescence analysis showed increased expressions of apoptotic markers like p53, Caspase3 and BAX by SNWE treatment. In conclusion, the findings of this study indicate the antiproliferative effect and apoptosis-inducing property of SNWE in both cell lines. Further studies are warranted on testing the anticancer activity of S. nigrum L. using animal models of cancer.